The Effectiveness of Different Natural Feeds on the Growth and Survival Juvenile of the Striped Snakehead Fish (Channa striata) - Hasan, Uswatul; Siswoyo, Bambang H; Manullang, Helentina M; Sari, Mutia; Rezeki, Indah Tri (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
One of the commodities of freshwater fish species that live in swamps and rivers that have high economic value is snakehead fish. In addition to having economic value, it also has a high albumin content and has various functions for health so it is very useful in the medical and industrial world. Snakehead fish is very rich in albumin, which is an important type of protein. There is 60% protein in plasma found in albumin, albumin in the blood functions to increase endurance, and is able to regulate the water balance in cells, waste products can also be removed, in the formation of new cells nutrients can be given so as to accelerate the recovery of body tissue that is split. post operation. The thing that must be considered at the time of feeding is the right amount, time and use. Therefore, the types of natural food that can be used as snakehead fish feed are silk worms (Tubifex sp), water fleas (Daphnia), small freshwater fish (gobies/tilapia). In this study, the design used was a non-factorial completely randomized design (CRD) with three treatments and three replications. From the results of the study, the highest growth of snakehead fish (Channa striata) was found in treatment A, namely absolute weight 6.61 grams, and average The average absolute length growth is 3.13 cm. The highest survival rate was in treatment A, which was 100% and the lowest was in treatment C, which was 76.6667%